Parental concern as an indicator of the severity of Obstructive Sleep Apnea in children. (September 2020) - Lavi, Mali; Tauman, Riva; Greenfeld, Michal; Fishman, Gadi; Wasserzug, Oshri; DeRowe, Ari
Abstract: Introduction: An accepted screening question for Obstructive Sleep Apnea (OSA) in children is "Does your child snore". However, this has no correlation to severity. The purpose of this study is to evaluate a simple 2-item questionnaire that reflects the degree of parental concern to predict the severity of Obstructive Sleep Apnea (OSA) in children as measured by Polysomnography (PSG). Methods: Prospective analysis of parental concern regarding their children referred for PSG due to suspected OSA. Parents of all study children completed the brief Parental Concern Scale (PCS) questionnaire that we devised and the validated Pediatric Sleep Questionnaire-Sleep-Related Breathing Disorder questionnaire (PSQ-SRBD). The PCS consisted of 1 question on the need for surgery and 1 question on concerns about the child's breathing. Both questionnaires were compared to PSG results. Results: Ninety-five children (mean age 4.2 ± 2.5 years, 52% males, mean body mass index z score 0.45 ± 1.8) were recruited. Twenty-three children (24%) had moderate-severe OSA and were referred for adenotonsillectomy. Correlations were found between the need for surgery score and the apnea-hypopnea index (r = 0.22, P  = .029), as well as the mean SpO2 levels (r = −0.24, P  = .02). The likelihood for the diagnosis of moderate-severe OSA by PSG increased as parental ranking for the need for surgery increased ( P  = .003). The need for surgery score was the only predictor for moderate-severe OSA ( P  = .039). Conclusion: Querying parents on their perception of their child's need for surgery is a practical, and easy-to-use tool that can help the clinician in prioritizing referral to PSG.